Methods of reducing soil movements for deep excavations in soft clay - Saravut Jaritngam. (2009)
Excessive ground movements in deep excavations have always been a major concern in urban development. The reduction of wall and ground movements in a deep excavation in clay can be achieved by (i) varying the design configurations (ii) treating the clay with jet grouting and (iii) treating the clay with deep mixing.